2012
DOI: 10.1111/j.1750-3841.2012.02849.x
|View full text |Cite
|
Sign up to set email alerts
|

Myrtus communis L. Infusions: The Effect of Infusion Time on Phytochemical Composition, Antioxidant, and Antimicrobial Activities

Abstract: In traditional medicine, myrtle (Myrtus communis L.) is frequently consumed as an infusion and decoction. In this study, we investigate the phenolic and volatile compositions and antioxidant and antibacterial activities of leaf infusions prepared during 3 different times. The total phenolics contents (146.74 to 179.55 mg GAE/g DM) varied significantly between infusions. Eleven phenolic compounds were identified by reversed-phase high-performance liquid chromatography. Phenolic acids (7.64 to 14.28 μmol/g DM) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 24 publications
(30 reference statements)
2
54
0
Order By: Relevance
“…10 This is due to the presence of bioactive compounds with innumerous biological activities reported in the literature such as antioxidant, hypotensive, antimicrobial, anti-inflammatory, hypoglycemic, and anticancer activities. 11 The most abundant compounds present in a Laboratory of Plant Biochemistry and Natural Products, Department of Biology, Faculty of Nature and Life Sciences, University of Oran 1, Ahmed Ben Bella, 1524EL M Naouer 31000 Oran, Algeria these species, mostly in the leaves, are phenolic compounds, such as flavonoids (myrecitin and quercetin glycoside derivatives, and flavan-3-ol derivatives) and phenolic acids (gallic, caffeic and ellagic acids). 10 In Algeria, there are two characteristic species of Myrtle: Myrtle communis L., the most known and common species in the Mediterranean area, being more abundant in the north of Algeria; and Myrtus nivelii Batt.…”
Section: Introductionmentioning
confidence: 99%
“…10 This is due to the presence of bioactive compounds with innumerous biological activities reported in the literature such as antioxidant, hypotensive, antimicrobial, anti-inflammatory, hypoglycemic, and anticancer activities. 11 The most abundant compounds present in a Laboratory of Plant Biochemistry and Natural Products, Department of Biology, Faculty of Nature and Life Sciences, University of Oran 1, Ahmed Ben Bella, 1524EL M Naouer 31000 Oran, Algeria these species, mostly in the leaves, are phenolic compounds, such as flavonoids (myrecitin and quercetin glycoside derivatives, and flavan-3-ol derivatives) and phenolic acids (gallic, caffeic and ellagic acids). 10 In Algeria, there are two characteristic species of Myrtle: Myrtle communis L., the most known and common species in the Mediterranean area, being more abundant in the north of Algeria; and Myrtus nivelii Batt.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when α-tocopherol was used, no additional loss effect against DPPH radical was observed. Several authors have determined the antiradical and antioxidant activities of hydrophilic fraction of EVOO by measuring the consumption of the DPPH radical (Minioti & Georgiou, 2010).The antioxidant activityphenolic compound content relationship was widely studied by several works, showing clearly that an increase in phenolic compound content correlated with a higher scavenging effect of the extract (Messaoud, Laabidi, & Boussaid, 2012).This could explain the highest scavenging activity of DPPH radicals by McPC-EEVOO extracts. Moreover, the enrichment of edible oil (as olive oil) by olive leaf extract increased significantly the scavenging effect against DPPH radical (Chiou, Kalogeropoulos, Salta, Efstathiou, & Andrikopoulos, 2009),and this observation may also support our finding.…”
Section: 1-diphenyl-2-picrylhydrazyl Radical (Dpph•) Assaymentioning
confidence: 97%
“…previously reported works, the phenolic compound composition of Italian (ARomani, Pinelli, Mulinacci, Vincieri, & Tattini, 1999) and Tunisian myrtle leaves (Wissem AidiWannes, Baya Mhamdi, Jazia Sriti, Mariem Ben Jemia, Olfa Ouchikh, Ghaith Hamdaoui, et al, 2010;Messaoud, Laabidi, & Boussaid, 2012) was examined and it was found the presence of different compounds belonging to the phenolic acid family, with gallic acid in Tunisian variety being more important than in the Italian variety. At 350 nm, we have also identified and quantified derivatives of myricetin in myrtle leaf extracts.The main important flavonoid detected was myricitrin (myricetin-3-O rhamnoside), identified by its retention time, spectral and fluorescence data in comparison with the standard.…”
mentioning
confidence: 96%
“…Although there are previous studies demonstrating antibacterial, anti-inflammatory, analgesic, antiproliferative and apoptotic effects of MC, the biological activities and potential molecular targets of its active compound, MC-A, are largely unknown [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%